SOX9 Knockdown-Mediated FOXO3 Downregulation Confers Neuroprotection Against Ischemic Brain Injury - Deng, Yiming; Ma, Gaoting; Gao, Feng; Sun, Xuan; Liu, Lian; Mo, Dapeng; Ma, Ning; Song, Ligang; Huo, Xiaochuan; He, Hongwei; Miao, Zhongrong (Frontiers in Cell and Developmental Biology, 2021)
Background: Evidence exists uncovering that SRY-box transcription factor 9 (SOX9) plays a role in ischemic brain injury (IBI). Thus, the current study was conducted to elucidate the specific role of SOX9 and mechanism by which SOX9 influenced IBI. Methods: The IBI-associated regulatory factors were searched by bioinformatics analysis. The rat model of IBI was generated using middle cerebral artery occlusion (MCAO) treatment. Neuronal cells were exposed to oxygen-glucose deprivation (OGD). The expression of SOX9, forkhead box O3 (FOXO3), transcription of Cbp/p300-interacting transactivator with Glu/Asp-rich carboxy-terminal domain 2 (CITED2), IκB kinase α (IKKα) in OGD-treated neuronal cells was characterized using RT-qPCR assay. The interaction among CITED2, IKKα and FOXO3 was identified by ChIP and dual luciferase reporter gene assay. Gain- and loss-of-function experiments were performed to verify the relationship among SOX9, FOXO3, CITED2, and IKKα and to investigate their functional effects on apoptosis and the inflammatory response of OGD-treated neuronal cells as well as neurological deficit and infarct area of the rat brain. Results: SOX9, FOXO3, CITED2 and IKKα were highly expressed in OGD-treated neuronal cells. Silencing of SOX9 inhibited OGD-induced neuronal apoptosis and inflammatory response and reduced the neurological deficit and infarct area of the brain in the rats caused by MCAO, but which were reversed by overexpressing of FOXO3, CITED2 or IKKα. Conclusion: Taken together, our study suggested that upregulation of SOX9 promoted IBI though upregulation of the FOXO3/CITED2/IKKα axis, highlighting a basic therapeutic consideration for IBI treatment.